Pengaruh Promo Jabatan, Keterlibatan Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT BPJS - Suwandy, Yauzra Abbiyuza; Hasibuan, Hasrul Azwar; Ahmad, Rizal (Universitas Negeri Medan, 2025)
This research was conducted at PT BPJS Health Medan with the aim of analyzing the influence of jobpromotions, work Engagement and work environment on employee job satisfaction. The research population was86 employees who worked in the company and the sample was taken with a saturated sample so that the totalsample was 86 respondents. The types of data used are primary and secondary data, data collection techniquesusing literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classicalassumption testing and hypothesis testing. The research results show that job promotion, Work Engagement andwork environment partially and simultaneously have a significant effect on employee job satisfaction. There is asufficient correlation between job promotion, work environment and organizational culture on employee jobsatisfaction in the company, amounting to 31.2% and the remaining 68.8% is explained by other variables notstudied.